PENGARUH DANA PIHAK KETIGA (DPK), RISIKO LIKUIDITAS DAN RISIKO PEMBIAYAAN TERHADAP PROFITABILITAS BSI KCP GAJAH MADA: LITERATURE REVIEW - Sriyono, Sriyono; Tri Tungga Dewi, Ayu; Nurul Hidayati, Fitriana; Rahma Maulida, Reva (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Sharia banks are an integral part of the world's financial system which is experiencing very rapid development so that it has a fairly high level of profitability. So if the higher the profitability of a bank, the better its performance will be. The level of profitability of a bank is influenced by several factors, for example due to the presence of third party funds (DPK), Liquidity Risk and Financing Risk. The design of this research is a Literature Review or literature review. Database searches using Google Scholar from 2020 to 2024. Secondary data sources in this research refer to books, scientific reports, articles from previous research. Search results on Google Scholar with the keywords "The influence of third party funds (DPK), liquidity risk and financing risk on profitability" found many relevant journals, so only 15 journals were taken for review. Third Party Funds have a positive and significant effect on BSI KCP's profitability Gajah Mada, Liquidity Risk has a positive and significant effect on the Profitability of BSI KCP Gajah Mada, Financing Risk has a positive and significant effect on the Profitability of BSI KCP Gajah Mada, Third Party Funds, Liquidity Risk, Financing Risk has a positive and significant effect on the Profitability of BSI KCP Gajah Mada Based on ideas Above, Third Party Funds (DPK) encourage bank profitability levels, because DPK acts as the main source of funding with lower costs. Liquidity risk is also a factor in increasing the profitability of BSI KCP Sidoarjo Gajah Mada because the liquidity risk management carried out is relatively good. In addition, financing risk is considered to increase the profitability of BSI KCP Sidoarjo Gajah Mada because it uses risk identification, measuring risk levels and developing appropriate mitigation strategies.